Developing an Assessment Model for Uncovering Potential Synergies of Regional Industrial Symbiosis: A Case Study of Valparaiso Region, Chile - Behzad-, M (Elsevier Ltd, 2024)
Waste management is considered as one of the main challenges of policy makers. In regional scale, industrial waste affects waste management planning as it requires strict policy control and implementation. Industrial symbiosis is known as a potential solution to reduce the volume of dumping waste by introducing the waste to input resources of the companies. This study contributes on developing a methodical framework on quantifying and ranking the synergy potential of symbiosis between companies in the industrial sector of Valparaiso region since it hosts major industrial activities in the central zone of Chile. The proposed methodology includes a waste-to-resource complementary arrangement which merges the waste database declared by the Chilean government with potential generation of new alternative resources and corresponding recipients. This methodology suggests two indicators to calculate the potential synergies: (1) number of connections between companies; (2) accumulated weight of waste-to-resource materials between companies. In total, 9582 connections and 62, 781, 963 tons of accumulated waste to resource materials between companies were identified in 5 territorial clusters. The results present a comparative basis of internal and external potential synergies identifying the pros and cons of each regional cluster. The assessment model developed for the Valparaiso region can be adapted to other regions in Chile or worldwide to quantify and rank the potential synergies to promote industrial symbiosis towards sustainable environment in macro scales. © 2024 Elsevier Ltd